STUDYING HUMAN DEVELOPMENT TO KNOW THE RIGHT LEARNING METHODS: MEMPELAJARI PERKEMBANGAN MANUSIA UNTUK MENGETAHUI METODE PEMBELAJARAN YANG TEPAT - Frezy Paputungan (LPPM UNiversitas Bina Mandiri Gorontalo, 2023)
Basically development refers to systematic changes in physical and psychological functions. Physical changes include basic biological development as a result of conception (fertilization of the ovum by sperm), and the result of the interaction of biological and genetic processes with the environment. Meanwhile, psychological changes involve the overall psychological characteristics of individuals, such as cognitive, emotional, social and moral development. Development can also be interpreted as